1998
DOI: 10.1159/000025568
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Stretch and Shear Stress: Physical Stimuli Determining the Production of Endothelium-Derived Relaxing Factors

Abstract: Mechanical forces generated at the endothelium by fluid shear stress and pulsatile stretch are important in ensuring the continuous release of vasoactive endothelial autacoids. Although the mechanism by which endothelial cells are able to detect and convert these physical stimuli into chemical signals is unclear, this process involves the activation of integrins, G proteins and cascades of protein kinases. The constitutive endothelial nitric oxide synthase (NOS III), classified as a Ca2+/calmodulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
156
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(160 citation statements)
references
References 103 publications
1
156
2
1
Order By: Relevance
“…Molecular biological studies have shown that a low average level, large gradients, and high oscillation of wall shear stress (WSS) contribute to atherosclerosis [1][2][3]. Therefore, the triggering of atherosclerosis by WSS is widely acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biological studies have shown that a low average level, large gradients, and high oscillation of wall shear stress (WSS) contribute to atherosclerosis [1][2][3]. Therefore, the triggering of atherosclerosis by WSS is widely acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that increased vascular wall shear stress associated with acute bouts of aerobic exercise may represent the main stimulus for vascular adaptations induced by chronic aerobic exercise (3,39,41). Accordingly, chronic aerobic exercise of moderate intensity is considered to have beneficial effects in cardiovascular diseases involving endothelial dysfunction (11,14,16,17).…”
mentioning
confidence: 99%
“…In this context, endothelium-dependent vasodilation induced by acetylcholine (ACh), which is known to produce NO-dependent vascular relaxation, has been used to characterize endothelium function in different physiological and pathophysiological conditions both in animal and human studies (7). Vascular reactivity can also be modulated by an endothelium-derived hyperpolarizing factor (EDHF), which probably acts through the activation of Ca 2ϩ -sensitive K ϩ channels (3). EDHF seems to be essentially involved in the local regulation of blood flow in small resistance vessels (10,37), with the exception of the coronary and renal vascular beds where it also contributes to the modulation of vascular reactivity in conduit arteries (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a correlation with changes in functional residual capacity (FRC) has led to the suggestion that mechanical stretching of lung tissue might be one underlying mechanism modulating lower airway NO formation (Str omberg et al 1997). Similar stretchresponsive mechanisms influencing NO release have been established in both striated muscle and endothelial cells (Awolesi et al 1995;Tidball et al 1998;Busse & Fleming, 1998). The amount of NO released from endothelial cells in response to a mechanical stimulus is determined by the timing and amplitude of the physical forces applied (Hutcheson & Griffith, 1991).…”
mentioning
confidence: 99%